Gender Perspective on Qur'an Surah An-Nisa, Verse 34 - Ahyat, Mahli; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The study of Qur’an Surah An-Nisa verse 34 often becomes a crucial point in understanding gender relations within Islam. Textually, the verse positions men as qawwam (caretakers or leaders) of the family; however, its interpretation has evolved from traditional exegesis toward more contextual readings that are inclusive and gender-just. This research employs a qualitative approach through library research and Abdullah Saeed’s contextual hermeneutics to analyze both classical and contemporary interpretations of the verse. The findings indicate that male leadership in this verse is functional, grounded in social and economic responsibilities, rather than a form of domination or moral superiority. Patriarchal interpretations have often restricted women’s roles, particularly in access to education, economic participation, and leadership. In contrast, inclusive interpretations emphasize that men and women share equal spiritual standing before God and that their social roles are complementary rather than hierarchical. Patriarchal culture and social constructions remain major challenges in achieving gender justice. Therefore, a reinterpretation of religious texts based on maqasid al-shariah is necessary to build a just and harmonious social structure. This study contributes to reinforcing the understanding that Islam, as a religion upholding justice and compassion, supports gender equality as an integral part of its values.